The system’s culture and transformations of pre-Islamic poetic discourse in Youssef Oulimat’s work - toumi, saida; Katt, Mustafa Bachir (El Omda in Linguistics and Discourse Analysis, 2025)
The experience of the critic Youssef Alimat in reading pre-Islamic poetry through his book "System Criticism / Representations of Patterns in Pre-Islamic Poetry" is a fertile and special experience, as it is a cultural approach in criticizing systems and revealing their implications. From studies on pre-Islamic poetry, cultural criticism emerged from the womb of cultural studies that worked to expand the horizon of analysis beyond the linguistic load and its aesthetic luster to the vastness of culture and its vast extensions.